Relationship between morphological characters, dry matter yield and fruit yield of cucumber - Eifediyi, E. K.; Remison , S. U.; Okaka, V. B. (Global Journal of Food and Agribusiness Management, 2012)
Field experiment was conducted during the wet season of 2008 at the Teaching and Research Farm of Ambrose Alli University, Ekpoma (Lat. 6° 45' North and Long. 6° 08' East and an altitude of 460 metres above sea level), to evaluate the relationship between farmyard manure, inorganic fertilizer and dry matter weights on the yield of cucumber. The experiment consisted of one variety of cucumber (Ashley), three farmyard manure rates and five fertilizer levels using a randomised complete block design fitted into a 3 × 5 factorial scheme with three replicates. The result of the study indicated that increasing the farmyard manure and fertilizer levels led to an increase in dry matter production and the yield of cucumber. There was a positive correlation between the total dry matter production and yield components of cucumber